Mewujudkan Kepuasan Wisatawan Karimunjawa dengan Pendampingan Pelayanan Prima Pramuwisata - Voettie Wisataone; Rosidah Rosidah; Nadia Sasmita Wijayanti (Warta LPM, 2022)
The tourism business is one of the pioneers of foreign exchange. The involvement of tour guides contributes to the progress of the tourism business. For this reason, tour guides need to demonstrate their quality of professional performance in the form of providing excellent service. Tourist satisfaction is a measure of service success. To maximize service potential, the community service team provides mentoring of excellent service for the Indonesian Tour Guides Association/ Himpunan Pramuwisata Indonesia (HPI) in Karimunjawa District. The program was carried out for three days and using the mentoring method. Mentoring begins with a workshop on the first day, by providing material related to excellent service. Afterward, live mentoring was carried out for two days. This community service is considered to be able to increase guide knowledge about excellent service and can evaluate guides when carrying out services. As many as 43.3% of participants fully understood the material presented and 53.3% of participants were able to practice excellent service well.